O (não) lugar da sensibilidade na formação do jurista docente - Casagrande, Aline (2023)
This thesis aims to direct the look at the contributory possibilities of the field of Philosophy of Education in the current training of teaching jurists, in particular for an influence that values the senses of experience as fundamental for a humanitarian and empathetic vision, beyond of the purely dogmatic technicality of Law. To this end, we sought to present the tensions and convergences of teaching in the baccalaureate, based on the (pre)concepts present in the academic culture, approaching professional development and the teaching identity, moving on to a reflective study of the process (de)training of the professor of Law. Then, the proposal was to add the concepts referring to violence(s) and their relationship with knowledge and reflections on training, relating their origin to the institutionalization of violence of Law by the State, in the resolution of social conflicts. The study was being developed from the existing observations in the work of Luis Alberto Warat, in particular from the theory he developed and called Pedagogy of Seduction for Law, from which it is presented as a possibility for the formation of jurists, in addition to of the restrictions imposed by the traditional view, the creation of a learning space as an environment of desire, with the teacher as an instigator of the process of academic protagonism. In this regard, the research sought support in pedagogical theories, which clarify the great paradigms of education, based on the differences in understanding regarding the participation of the subject from different schools (namely: technicist, Marxist, social critic, constructivist and new school). To carry out the research developed, a qualitative approach was used, in which the type of research was constituted in part as a theoretical-bibliographic hermeneutic nature, followed by self-reflection research on teaching performance, over fifteen years of experience in the area of legal training, seeking a hermeneutic contemplation of the narrative itself